Motivational factors shaping Muslim students’ decisions to study abroad: A case study of Northern Cyprus - Bayraktar, Fetine; Yorganci, Ilkay (Journal of International Students, 2025)
This study investigates the motivational factors influencing Muslim students’ decisions to pursue higher education in Northern Cyprus, with a focus on the interplay of cultural, religious, and academic considerations. Drawing on data from two leading institutions from North Cyprus, We explore students’ academic, social, and cultural experiences within the context of educational tourism. Key drivers identified include the perceived quality of education, economic affordability, and the culturally safe environment offered by Northern Cyprus. While participants reported personal and professional growth, challenges such as limited cultural integration and restricted employment opportunities were highlighted. The findings provide actionable insights for universities and policymakers to enhance recruitment strategies and tailor support services to meet Muslim international students’ needs better.